Estimasi Biaya dan Evaluasi Program Intervensi Pemberian Pangan Olahan untuk Keperluan Medis Khusus (PKMK) untuk Perbaikan Status Gizi di Banyumas, Jawa Tengah - Hasnur, Hanifah; Presilawati, Febyolla (UI Scholars Hub, 2021)
The Government of Banyumas has implemented an intervention in the Provision of Processed Food for Special Medical Purposes (FSMP) with nutritional supplementation of 1.5 kcal/mL in 2019. However, there is no evaluation has been carried out, both of outcome and the cost of the intervention. So that, it is necessary to provide an initial picture of the resources needed for the formulation of future intervention plans. This study aims to determine the estimated cost required for FSMP intervention and to determine the outcome of the intervention. The economic evaluation was carried out partially by calculating costs from the perspective of the program implementing institution and the outcome of the intervention in the form of increasing weight and height. The research sample was 40 toddlers who had been selected based on nutritional screening of toddlers who were unable to consume existing foods and had inadequate nutritional intake. The results of the study showed that the total intervention cost was Rp.219.817.000 for 40 children (Rp.5.495.438 per child) where for nutritional supplementation of 1.5 kcal/mL per child was Rp.1.395.850. There was an increase in the average weight and height of children by 0.64-kilogram and 0.47-centimeter in 28 days after the program was completed. The estimated cost from the results of this study could be lower in subsequent interventions if the equipment is reused. This study can be used as a reference for FSMP interventions with the same subject coverage/criteria or on a wider scale.